Refleksje o przedmiocie podatku dochodowego - Filipczyk, Hanna (Kwartalnik Prawa Podatkowego, 2015)
The paper discusses the problem of how the object and scope of income tax should be determined. Despite inherent difficulties in doing so, caused by the normative (legal) concept of income, its economic concept and income itself inevitably diverging (ectopia thesis; J. Prebble, B. Brzeziński), establishing the legal concept of income is indispensable in the operative interpretation and application of income tax laws provisions. It is akin to the Haig-Simons concept of income, being its adaptation – subject to modifications resulting from its legal conventionalisation. It is appropriate to use this concept in determining the object and scope of income taxation. Theoretical conclusions are illustrated by the analysis of the position of administrative courts on tax implications of the dividend distribution in kind.